Analysis of Differences in the Signal Reflected from an Aircraft and Simulated Interference in an Application to Radar Protection - S. R. Heister; Huang Qianlan (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2024)
The creation of DRFM (Digital Radio Frequency Memory) technology is a revolutionary step in the development of simulating interference techniques. The technology made it possible to transform the received signal with high quality, make the necessary changes to it and emit it in the form of simulating interference. Currently, a high level of imitation of radar signals reflected from real objects has been achieved. The basis for counteracting such interference is a detailed analysis of the differences between the real reflected signal and simulating interference. In this regard, a mathematical model of a signal reflected from a spatially distributed object is considered before and after frequency conversion to video frequency. Based on the analysis of typical variants of interference generation, mathematical models of simulating interference are considered, providing various degrees of similarity to the reflected signal. The results of the model analysis are the basis for constructing algorithms for protecting radar stations from simulating interference.